An evidence-based toolbox for the design and implementation of selective-prevention primary-care initiatives targeting cardio-metabolic disease - Sonderlund, Anders Larrabee; Thilsing, Trine; Korevaar, Joke; Hollander, Monika; Lionis, Christos; Schellevis, Francois; Wändell, Per; Carlsson, Axel C; de Waard, Anne-Karien; de Wit, Niek; Seifert, Bohumil; Angelaki, Agapi; et al. (Preventive medicine reports, 2019)
Cardio-metabolic diseases (CMD; cardiovascular disease, type 2 diabetes, chronic kidney disease) represent a global public health problem. Worldwide, nearly half a billion people are currently diagnosed with diabetes, and cardiovascular disease is the leading cause of death. Most of these diseases can be assuaged/prevented through behavior change. However, the best way to implement preventive interventions is unclear. We aim to fill this knowledge gap by creating an evidence-based and adaptable "toolbox" for the design and implementation of selective prevention initiatives (SPI) targeting CMD. We built our toolbox based on evidence from a pan-European research project on primary-care SPIs targeting CMD. The evidence includes (1) two systematic reviews and two surveys of patient and general practitioner barriers and facilitators of engaging with SPIs, (2) a consensus meeting with leading experts to establish optimal SPI design, and (3) a feasibility study of a generic, evidence-based primary-care SPI protocol in five European countries. Our results related primarily to the five different national health-care contexts from which we derived our data. On this basis, we generated 12 general recommendations for how best to design and implement CMD-SPIs in primary care. We supplement our recommendations with practical, evidence-based suggestions for how each recommendation might best be heeded. The toolbox is generic and adaptable to various national and systemic settings by clinicians and policy makers alike. However, our product needs to be kept up-to-date to be effective and we implore future research to add relevant tools as they are developed.
Keywords: Lifestyle-related disease; Behavior change; Primary care; Cardiovascular disease; Prevention; Self-efficacy; Preventive health care